Using the rapid alert system for food and feed: potential benefits and problems on data interpretation. Issue 6 (26th March 2021) - Kowalska, Aleksandra; Manning, Louise
Abstract: The Rapid Alert System for Food and Feed (RASFF), where competent authorities in each Member State (MS) submit notifications on the withdrawal of unsafe or illegal products from the market, makes a significant contribution to food safety control in the European Union. The aim of this paper is to frame the potential challenges of interpreting and then acting upon the dataset contained within the RASFF system. As it is largest cause of RASFF notifications, the lens of enquiry used is mycotoxin contamination. The methodological approach is to firstly iteratively review existing literature to frame the problem, and then to interrogate the RASFF system and analyze the data available. Findings are that caution should be exercised in using the RASFF database both as a predictive tool and for trend analysis, because iterative changes in food law impact on the frequency of regulatory sampling associated with border and inland regulatory checks. The study highlights the variability of engagement by MSs with the RASFF database, influencing generalisability of the trends noted. As importing countries raise market standards, there are wider food safety implications for the exporting countries themselves. As this is one of the first studies articulating the complexities and opportunities of using the RASFF database, this research makes a strong contribution to literature.